2022
DOI: 10.3390/ijerph192316020
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Two Screening Tools for Detecting Delirium in Older Patients in the Post-Anaesthetic Care Unit: A Diagnostic Test Accuracy Study

Abstract: (1) Background: Delirium is a common complication among surgical patients after major surgery, but it is often underdiagnosed in the post-anaesthetic care unit (PACU). Valid and reliable tools are required for improving diagnoses of delirium. The objective of this study was to evaluate the diagnostic test accuracy of the Three-Minute Diagnostic Interview for Confusion Assessment Method (3D-CAM) and the 4A’s Test (4AT) as screening tools for detection of delirium in older people in the PACU. (2) Methods: A pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…In addition, it was found to improve delirium diagnosis [21], especially in older patients [36]. Moreover, it can be used in different departments, such as emergency units of various wards [34] and PACU [37]. However, the 4AT has a significant false-positive rate in this initial comparison, which may need further in-depth examinations [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it was found to improve delirium diagnosis [21], especially in older patients [36]. Moreover, it can be used in different departments, such as emergency units of various wards [34] and PACU [37]. However, the 4AT has a significant false-positive rate in this initial comparison, which may need further in-depth examinations [19].…”
Section: Discussionmentioning
confidence: 99%
“…Studies were reported from 10 different countries from Asia, Europe, Australia, and Canada (Fig. 2), including Iran [33], Canada [34], UK [21], Germany [35], Italy [36], Sewden [14], Norway [22], Australia [37], Spain [38] and Switzerland [19] (Fig. 2).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations